Transplacental passage of hyperforin, hypericin, and valerenic acid - Spiess, Deborah; Abegg, Vanessa Fabienne; Chauveau, Antoine; Rath, Joshua; Treyer, Andrea; Reinehr, Michael; Kuoni, Sabrina; Oufir, Mouhssin; Potterat, Olivier; Hamburger, Matthias; Simões-Wüst, Ana Paula (Frontiers in Pharmacology, 2023)
Safe medications for mild mental diseases in pregnancy are needed. Phytomedicines from St. John’s wort and valerian are valid candidates, but safety data in pregnancy are lacking. The transplacental transport of hyperforin and hypericin (from St. John’s wort), and valerenic acid (from valerian) was evaluated using the ex vivo cotyledon perfusion model (4 h perfusions, term placentae) and, in part, the in vitro Transwell assay with BeWo b30 cells. Antipyrine was used for comparison in both models. U(H)PLC-MS/MS bioanalytical methods were developed to quantify the compounds. Perfusion data obtained with term placentae showed that only minor amounts of hyperforin passed into the foetal circuit, while hypericin did not cross the placental barrier and valerenic acid equilibrated between the maternal and foetal compartments. None of the investigated compounds affected metabolic, functional, and histopathological parameters of the placenta during the perfusion experiments. Data from the Transwell model suggested that valerenic acid does not cross the placental cell layer.